2014
DOI: 10.1186/s12905-014-0156-z
|View full text |Cite|
|
Sign up to set email alerts
|

Does South Korea have hidden female smokers: discrepancies in smoking rates between self-reports and urinary cotinine level

Abstract: BackgroundFemale smoking is perceived very negatively in East Asian countries such as South Korea, Japan, and China, as well as in Islamic countries. These countries’ self-reported surveys (SRs) tend to produce results that underestimate the number of smokers, owing to the social desirability response bias. The present study seeks to assess South Korea, Europe, and the Americas, by comparing data from SRs with those from urinary cotinine samples.MethodsCurrent smoking rates were calculated using the SRs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 17 publications
1
68
3
Order By: Relevance
“…The association has shown to be prevalently non-linear for CPI ≥ 3 case definition models, and conversely prevalently linear for CPI = 4 models. Since the association became linear after restricting to females also in CPI ≥ 3 model, a possible explanation could be that the non-linear association observed in the total population was also in this case due to residual confounding by smoking (Korean women have low cigarette smoking rate, contrary to Korean men - Park et al 2014). However, it is not possible to exclude that the non-linear association was due to other factors, such as a direct biological effect of sleep duration on periodontitis or viceversa.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The association has shown to be prevalently non-linear for CPI ≥ 3 case definition models, and conversely prevalently linear for CPI = 4 models. Since the association became linear after restricting to females also in CPI ≥ 3 model, a possible explanation could be that the non-linear association observed in the total population was also in this case due to residual confounding by smoking (Korean women have low cigarette smoking rate, contrary to Korean men - Park et al 2014). However, it is not possible to exclude that the non-linear association was due to other factors, such as a direct biological effect of sleep duration on periodontitis or viceversa.…”
Section: Discussionmentioning
confidence: 90%
“…The reasons of these effect modifications need to be further investigated, but the reduction of the estimate for some subgroups could be at least in part related to residual confounding of smoking (e.g. in current smokers, males and higher lead blood levels) (Mannino et al 2005, Park et al 2014. The association has shown to be prevalently non-linear for CPI ≥ 3 case definition models, and conversely prevalently linear for CPI = 4 models.…”
Section: Discussionmentioning
confidence: 99%
“…4 Park et al measured the female smoking rate with urine cotinine concentrations and found that the female smoking rate in Korea was 18.2%, triple the self-reported smoking rate. In particular, women in their 30s had a biochemical test smoking rate that was three times higher than their self-reported smoking rate 3. The female smoking rate in Korea, as determined by urine cotinine concentration, is higher than the average female smoking rate of OECD countries.…”
Section: Introductionmentioning
confidence: 86%
“…Since East Asian countries have especially strong negative perceptions of women smokers, they tend not to let other people around them know about their smoking 24 18 19 According to Park et al ,3 a higher proportion of females hid their smoking than males, and one out of every two female smokers hid their smoking behaviour in self-reported questionnaire surveys. Since the self-reported smoking rate is likely to be underestimated, biochemical tests are required in addition to self-reported questionnaires in order to determine the exact relationship between smoking and laryngeal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This study used current smokers in Korean men, who account for most smokers in Korea. Females may not accurately report smoking status because of cultural reason [14]. Therefore we used 2,972 subjects who were current smokers among men aged 18 and older in 2009 as a baseline.…”
Section: Methodsmentioning
confidence: 99%